Efeito do β-glucano dietético na dinâmica metabólica, na resposta imunológica inata e no desempenho do pacu (Piaractus mesopotamicus) após ciclos curtos de jejum e realimentação - Corredor-Castillo, Adriana Soliris [UNESP] (2016)
The objective of this study was to evaluate the effect of oral administration of β-glucan on growth, feed utilization, metabolic dynamics and the innate immune responses of pacu (Piaractus mesopotamicus) subjected to short-term starvation and refeeding and the immunostimulatory action of β-glucan offered for 15 days in the final phase of the cycle. A total of 210 fish was distributed in 21 tanks and submitted to different feeding strategies for seven weeks: GC - feeding daily with commercial feed (RC); G 6/1- 6-day feeding with RC and 1 restraint day (6/1); G 2/1 - 2-day feeding with RC and 1 restraint day (2/1); GCS - Feeding daily with RC and supplemented with 0.5% β-glucan (RCS) in the last 15 days; GS 6/1 - 6-day feeding with RC and 1 restraint day, and RCS in the last 15 days; GS 2/1 - 2-day feeding with RC and 1 restraint day, and RCS in the last 15 days. A seventh group (GC-PBS) was fed every day to control the effect of the handling and bacterial inoculation (injected PBS control). On day 50, nine fish of each treatment were sampled, weighed and anaesthetized with benzocaine (1.0g / 15L water) for blood, liver, white muscle and foregut sampling, to determine the specific growth rate (SGR), feed conversion (CA), morphology of intestinal mucosa, concentration of circulating and tissue metabolites, leukocyte respiratory burst, serum lysozyme concentrations, serum hemolytic activity of complement system (alternative pathway), total leukocyte differential count and intestinal leukocyte infiltration (ILI). The remaining fish were inoculated with A. hydrophila, and the injected PBS control group received only PBS. Nine fish per treatment were sampled at three and 24 hours after inoculation. The results showed that the specific growth rate was lower in the fish G 2/1 and feed conversion was better in all fish fed with 0.5% β-glucan. In fish G 2/1, blood glucose levels and non-esterified fatty acids were higher and triglyceride levels were lower Liver glycogen and lipid concentrations and lipid muscle concentration gradually decreased in fish G 6/1 and G 2/1 in relation to the CG showing higher mobilization of energy in liver and muscle. Length of intestinal villi was lower in fish 2/1, and the number of goblet cells decreased with the severity of feed restriction while β-glucan increased this number, including in control fish. Food restriction affected the immune response, reducing the leukocyte respiratory activity, and the serum lysozyme. The β-glucan supplementation improved immune response, increasing ARL, AHC, lysozyme, defense cell count and ILI. Bacterial infection increased neutrophils and monocytes and decreased lymphocytes, while the β-glucan increased lymphocytes, decreased neutrophils and potentiated the increase of monocytes and increased the number of special granulocytic cells. There was a progressive decrease in ILI as the frequency of fasting increased, but the β-glucan reversed this decrease, including in control fish. In conclusion, feeding strategies, although had affected negatively some indicators of the innate immune system, they did not avoid the response of this system to a bacterial challenge. In conclusion, feeding strategies, although had affected negatively some indicators of the innate immune system, they did not avoid the response of this system to a bacterial challenge. β-glucan supplementation improved the utilization of food by pacu, independent on the feeding strategy, and improved their immune response against challenge with Aeromonas hydrophila.